Lessons About Autonomy and Integration from International Human Rights, Law Journals, and the World of Golf - Bruch, Elizabeth M. (Columbia Journal of Gender and Law, 2003)
In this essay I will consider the questions posed by the symposium-“why have a feminist law journal?” and the specific question of this panel, “which master, autonomy or integration, do we or should we serve?”–together with the parallel questions that arise in the debate among international human rights advocates and scholars about whether to address women’s human rights issues separately from “mainstream” human rights. However, I want to begin on a slightly different (but not unrelated) topic: women and sports. I am relatively newly married and, in one of those important early negotiations of couplehood, I agreed to let my husband educate me about golf; in return, he has agreed to develop a deeper appreciation for feminist theory. Our interests have coincided in a series of recent events in the sporting world. Let me provide just a few highlights. In May of this year, Annika Sorenstam, often called “the world’s most dominant female golfer,” participated in the Colonial Invitational, an event on the Professional Golfers’ Association (PGA) Tour. Sorenstam played from the same tees as the men, with no special accommodations. According to the Washington Post, her decision to play the event “touched off debate among men and women over whether the experiment is good for the sport and whether Sorenstam can ultimately compete.” It touched off that same debate in my house. Other versions of this drama are playing out elsewhere in the world of golf and have provoked significant emotion, especially if accommodations, such as closer tees, are made for women.